Population, nesting characteristics, and breeding ecology of the critically endangered Gyps indicus in Mudumalai Tiger Reserve, South India - Arockianathan Samson; Jabamalainathan L. Princy; Balasundaram Ramakrishnan (Nature Conservation Research: Заповедная наука)
The species extinction rate has recently accelerated worldwide and is a thousand times higher than through natural processes alone. Small, isolated populations are especially vulnerable to extinction due to deterministic and stochastic threats. Hence, the conservation of such populations is challenging. The present study from 2015 to 2021 aimed to understand the population, nesting characteristics, and breeding ecology of the country's southernmost population of Gyps indicus in Mudumalai Tiger Reserve, South India. The population estimation was performed on the roosting and nesting sites of Gyps indicus in the Mudumalai Tiger Reserve. To study the nesting characteristics and breeding ecology, each nesting colony was systematically visited four times per month during the breeding season (October to May). Assessments of threats were estimated during the field visits. In 2015–2021, four breeding sites were identified. Two nesting sites were identified in 2016 and two more in 2017 and 2020. The mean altitude of the nesting sites was 1122.25 ± 170.06 m a.s.l., ranging from 821 m a.s.l. to 1600 m a.s.l. In the Protected Area, two nests were located on east-facing exposure, one nest on southeast-facing exposure, and one nest on south-facing exposure. In terms of population composition, the mean number of adult individuals steadily increased from 9.5 ± 0.46 in 2016 to 14.08 ± 0.67 in 2021. Consequently, the mean total number of individuals per colony increased from 13.66 ± 0.56 in 2016 to 27.83 ± 0.62 in 2021. A total of 40 (in average, 6.66 ± 0.49 pairs/year) territorial pairs with occupied nests were observed in 2015–2021. Of them, 31 (in average, 5.16 ± 0.30 pairs/year) breeding pairs had laid eggs. Successful incubation was recorded, and the mean incubation period was 63.64 ± 1.74 days. Out of 31 incubated nests, 23 fledglings (3.83 ± 0.47 individuals/year) successfully came out with 74% breeding success. The entire nesting period was 128.43 ± 1.16 days. In total, out of 17 failed breeding attempts nine (53%) were detected before egg laying, and eight (47%) were found during incubation. There were no significant differences between nests abandoned before and after egg laying (t = 0.4152, p > 0.05). During the breeding seasons of 2015–2017, a human-made forest fire posed a serious threat to nesting colonies of Gyps indicus, resulting in no observed nesting. A species-specific conservation-oriented action programme is necessary to secure this last southernmost wild viable Gyps indicus population in the Mudumalai Tiger Reserve. At this juncture, we highly recommend declaring the buffer zone of the Mudumalai Tiger Reserve as a «Vulture Sanctuary» to provide a legal protection of the Gyps indicus population living in the studied area.